The Influence of College Physical Education on Sports Industry Economy - Peng, Keshun; Li, Guangye; Zhang, Jianliang; Zhang, Meng (International Journal of Social Sciences and Public Administration, 2024)
With the promotion of national emphasis on physical education and the vigorous development of sports industry economy, the role of physical education in colleges and universities is increasingly prominent. The purpose of this paper is to explore the influence of college physical education on the economic development of sports industry, analyze the internal relationship between college physical education and sports industry economy, and provide theoretical support for the reform and development of college physical education. This paper mainly uses the method of literature analysis, through the combing of relevant literature, to understand some universities and sports enterprises online, and to conduct scientific comprehensive analysis of the collected information. It is found that physical education in colleges and universities has an important impact on the development of sports industry economy. On the one hand, college physical education has trained a large number of sports professionals, which provides human resources support for the sports industry; On the other hand, the construction and operation of sports facilities in colleges and universities has also driven the demand for related sports products and services, and promoted the development of the sports industry. In addition, the holding of sports events and activities in colleges and universities has also led to the development of related industries such as spectator and tourism. Therefore, strengthen the deep integration of college physical education and sports industry, and give full play to the leading role of college physical education in the development of sports industry.